THE APPLICATION OF CLASSDOJO APPLICATION IN ASSESSMENT OF STUDENT ATTITUDE - Tentiyo Suharto; Ahmad Salman Farid; Muhammad Ardiansyah; Dina Syarifah Nasution (Bajang Institute, 2021)
Education is an effort to create quality human beings and shape human character itself. This is what makes humans cannot be separated from education and makes education a necessity for all time. Education itself has a system that consists of input, process and output. The output of education is to create quality human beings, this can be measured by good learning achievement. Learning achievement is the maximum benchmark that has been achieved by students after conducting lecture activities for a predetermined time including the value of good student attitudes. Classdojo is a free internet-based application that provides many features and facilitates its users to find out student activities or the development of student attitudes in real time. The background of the problem in this research is how is the implementation of the Classdojo application in calculating student behavior? How is the change in student attitudes in implementing the Classdojo application? The theoretical studies in this research are Learning and Learning Media Development, Classdojo-Based Learning Media Development, Educational Technology Concepts, Assessment Theory, Attitude Change Theory. While the Type of Research This type of research is a qualitative research by conducting case studies to several State Universities in North Sumatra, including the State Islamic University of North Sumatra, Padangsidimpuan State Islamic Institute and the University of North Sumatra. This research is one of the most effective ways to develop and even advance an application system for assessing student attitudes.The results of the research from the analysis above, Attitudes in general are feelings, thoughts, and tendencies of a person who are more or less permanent in recognizing certain aspects in their environment. The components of attitude are knowledge. feelings, and tendencies to act. The response in question can be in the form of actions or actions that can be observed and can be in the form of intentions or intentions to perform certain actions in relation to the object of attitude. The application of the clasdojo application to the assessment of student attitudes both cognitively, affectively and conatively is very beneficial and the changes experienced by students, especially in the application of positive attitudes.